1981
DOI: 10.1172/jci110163
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of nicotinamide adenine dinucleotide as an intracellular regulator of renal transport of phosphate in the rat.

Abstract: A B S T R A C T In these experiments we investigated whether NAD could serve as an intracellular modulator of the brush border membrane (BBM) transport of inorganic phosphate (Pi). NAD, both oxidized (NAD+) and reduced (NADH) form, inhibited the Na+-dependent uptake of 32Pi in the concentration range of 10-300 zM NAD when added in vitro to BBM vesicles isolated from rat kidney cortex, but did not inhibit BBM uptake of D-[3H]glucose or BBM uptake of 22Na+. Neither nicotinamide (NiAm) nor adenosine alone influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…A pharmacologic dose of NAM inhibits renal and intestinal Na/Pi transport activity in normal rats. 15,16 In those animals, cellular NAD levels are increased in inverse proportion to Na/Pi transport activity. 16 Indeed, we showed that NaPi-II protein levels were markedly decreased and NAD concentrations were increased at kidney in PH animals, suggesting that the effects were similar to those in NAM-treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A pharmacologic dose of NAM inhibits renal and intestinal Na/Pi transport activity in normal rats. 15,16 In those animals, cellular NAD levels are increased in inverse proportion to Na/Pi transport activity. 16 Indeed, we showed that NaPi-II protein levels were markedly decreased and NAD concentrations were increased at kidney in PH animals, suggesting that the effects were similar to those in NAM-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In those animals, cellular NAD levels are increased in inverse proportion to Na/Pi transport activity. 16 Indeed, we showed that NaPi-II protein levels were markedly decreased and NAD concentrations were increased at kidney in PH animals, suggesting that the effects were similar to those in NAM-treated animals. NAM concentrations in the urine of PH rats, however, were approximately 10 times lower than those in the rats administered a pharmacologic dose of NAM (1 g/kg body weight; Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of Na'-H' exchange was determined by using a rapid filtration technique (23,24), basically as described by Frieberg et al (19), except that we employed BBMVs prepared by the calcium precipitation method, and that the pH of the intravesicular medium was pH 6.0 instead of 5.5. In the experiments when Na+-H+ exchange across the BBM was measured, BBMVs were prepared as in other solute uptake studies (18)(19)(20), but were preloaded (13) (12)(13)(14)(15). Because the Na+-H+ antiport in the renal BBM is specifically blocked by amiloride (17), the 22Na' uptake at pH gradient condition (pHi < pHO) was always measured simultaneously with and without addition of I mM amiloride, the maximum inhibitory concentration of the compound (17).…”
Section: Methodsmentioning
confidence: 99%